STUDENTS ABILITY IN LISTENING COMPREHENSION OF ELEVENTH GRADE AT MAN 2 MODEL MEDAN - Aisyah Amini Tanjung; Lisna Aulia Shalsabilla; Muhammad Riski Agung; Nurhasanah (Cemara Education and Science, 2024)
The research conducted at MAN 2 MODEL Medan aimed to assess the listening comprehension abilities of eleventh-grade students during the academic year 2024/2025. Utilizing a descriptive quantitative research design, data was collected through a listening comprehension test administered to Class XI F1D students. The test covered various topics, each with a set of multiple-choice questions. Analysis of the test results revealed an average listening comprehension ability of 83.6, categorized as good based on predetermined criteria. Further classification of student achievement demonstrated that the majority of students exceeded the minimum standards, with only a small percentage falling below. These findings indicate a positive outcome in students' listening abilities and highlight the effectiveness of listening comprehension tests in assessing language skills. This research contributes to understanding the current state of listening comprehension skills among eleventh-grade students at MAN 2 MODEL Medan.